Penggunaan Peranti Ortodonti Lepasan dalam Mengoreksi Diastema Anterior Rahang Atas dan Gigi Berjejal Rahang Bawah - Nelvi Yohana; Aninda Putri Mulyani; Aria Fransiska (Faculty of Dentistry Universitas Andalas, 2024)
Introduction: Malocclusion is one of the most common dental and oral health issues encountered in the community, with a prevalence of up to 80% of the population. Some patients prefer malocclusion treatment using devices that are removable by the patient, easy to clean, and relatively affordable. Removable orthodontic appliances have been proven effective in correcting simple dental malocclusions, resulting in well-aligned teeth, improved facial aesthetics, and stable long-term outcomes. Case Report: A 23-year-old male patient visited RSGM Unand to align his teeth. Clinical examination revealed anterior diastema in the upper jaw and crowding in the lower anterior jaw. He had a Class I Angle molar relationship and a Class I canine relationship with an overjet of 2.4 mm and an overbite of 2.3 mm. Management: The patient was treated with a removable orthodontic appliance with several active components, including a labial bow, T- springs, and Z-springs. Follow-up appointments were conducted once a week. After 11 follow-up sessions, the malocclusion was corrected. Conclusion: This case demonstrates the success of treatment using a removable orthodontic appliance, which improved the patient's stomatognathic function and aesthetics.